Electrochemical characterization of PbO2-TiO2 composite prepared on stainless steel substrate by cyclic voltammetry method - Tot, Pham Thi; Thuy, Mai Thi Thanh; Binh, Phan Thi (Vietnam Journal of Science and Technology, 2022)
In this study, PbO2-TiO2 composite was prepared on stainless steel (SS) substrate by cyclic voltammetry (CV) method from mixed solution containing TiO2 sol-gel with size from 10 to 50 nm. In the electrochemical deposition, TiO2 nanoparticle will disperse in the growing PbO2 coating to create PbO2-TiO2 composite. These TiO2 nanoparticles are delivered from the electrolyte bulk to the eletrode surface by diffusion and migration.The electrochemical properties of SS/PbO2-TiO2 electrodes were investigated in 0.5 M H2SO4 solution by CV, PP (potentiodynamic polarization), and EIS (electrochemical impedance spectroscopy) methods with and without UV irradiation. The results showed that the exchange current density (io), the value o (ip,a and ip,c, respectively) depended on the TiO2 concentration. With a solution containing  2 g/L TiO2, the value of the redox peaks is the largest and the exchange current density obtained is close the maximum value, indicating that the SS/PbO2-TiO2 composite electrode exhibits the best electrochemical activity under this solution condition. Due to the presence of TiO2 in the composite, the height of the redox peaks and the exchange current density increased sharply under UV light. This demonstrated that the photo-electrochemical activity of the composite is very good, which  can be used  to remove  dyes in wastewater by electrocatalytic oxidation.